Develop A Decision-Making Strategy for Sustainable WWTP Locations Using FAHP: Baghdad a Case Study (Journal of Engineering, 2025)
Population growth and urban development have posed challenges for wastewater treatment plants (WWTPs) locations in large cities such as Baghdad since they fail to meet sustainability criteria due to outdated planning and the lack of an approved strategy to determine the appropriate location for a WWTP in it. This study aims to develop a decision-making strategy for sustainable sites for WWTPs by using the Fuzzy Analytic Hierarchy Process (FAHP) and applying the strategy to evaluate the locations of the major WWTPs in Baghdad. Nine factors affecting decision-making regarding WWTP locations were categorized into three groups based on environmental, economic, and social sustainability requirements. A questionnaire method was used to collect data and calculate weights for each factor from the opinions of 12 experts. Seven factors had weight values greater than zero, while two had zero values and were excluded. A second questionnaire calculated the distance distribution for each factor, with experts agreeing on the ratings. Three equations for calculating main group weights and one for total weights have been developed using the weighted factors. The equations were applied to evaluate the locations of Baghdad's major WWTPs, Al-Karkh, Al-Rustamiya Southern, and Al-Rustamiya Northern. The results showed that the three locations were unsuitable due to limitations in distance from population settlements, main and secondary roads, and surface water bodies at Al-Rustamiya Southern and Northern WWTP locations.